Reduced-complexity turbo equalization for high-density magnetic recording systems - P. Supnithi; R. Lopes; S.W. McLaughlin (My University, 2003)
This paper considers a decision-feedback-equalizer (DFE)-based soft decision detector as an alternative for the Bahl-Cocke-Jelinek-Raviv (BCJR) front-end for a coded magnetic recording channel. In previous work, a bidirectional-arbitrated DFE (BAD) was shown to perform in between a BCJR detector and a minimum mean-square error DFE. We propose a soft-output BAD (S-BAD) which takes advantage of the original structure and is suitable for iterative decoding when used with outer codes. We show that with a convolutional code as an outer code, S-BAD performs close to higher complexity detectors.
Keywords: Turbo; BCJR algorithm; Turbo code; Convolutional code; Turbo equalizer; Code (set theory); Error Correcting Code Techniques